Antibacterial activity and effects of Colla corii asini on Salmonella typhimurium invasion in vitro and in vivo - Kwang-il Park; Mi-ra Lee; Tae-woo Oh; Kwang-Youn Kim; Jin-yeul Ma (BMC, 2017)
Abstract Background Salmonella enterica serovar Typhimurium is a foodborne pathogen that triggers inflammatory responses in the intestines of humans and livestock. Colla corii asini is a traditional medicine used to treat gynecologic and chronic diseases in Korea and China. However, the antibacterial activity of Colla corii asini has been unknown. In this study, we investigated the antibacterial activity and effects of Colla corii asini extract on Salmonella typhimurium invasion. Methods To tested for antibacterial effects of Colla corii asini extracts, we confirmed the agar diffusion using Luria solid broth medium. Also, we determined the MIC (minimum inhibitory concentration) and the MBC (minimum bactericidal concentration) value of the Colla corii asini ethanol extract (CEE) by using two-fold serial dilution methods. We evaluated the expression of salmonella invasion proteins including SipA, SipB and SipC by using Western blot and qPCR at the concentration of CEE without inhibition of bacterial growth. In vitro and vivo, we determined the inhibitory effect of invasion of S. typhimurium on CEE by using gentamicin assay and S. typhimurium-infected mice. Results CEE significantly inhibited the growth of Salmonella typhimurium in an agar diffuse assay and had an MIC of 0.78 mg/ml and an MBC of 1.56 mg/ml. Additionally, CEE reduced Salmonella typhimurium cell invasion via the inhibition of Salmonella typhimurium invasion proteins, such as SipA, SipB and SipC. Furthermore, CEE significantly suppressed invasion in the small intestines (ilea) of mice injected with Salmonella typhimurium. Conclusion These findings show that Colla corii asini exerts antibacterial activity and suppresses Salmonella typhimurium invasion in vitro and in vivo. Together, these findings demonstrate that Colla corii asini is a potentially useful therapeutic herbal medicine for treating salmonella-mediated diseases.